Evaluation of heart work as a prediagnostic tool using the modified Windkessel model and different whole blood viscosity models. (31st July 2012) - Suh, S.H.; Kaptan, Y.; Roh, H.W.; Kwon, H.M.; Lee, B.K.
The cardiovascular diseases, especially the atherosclerosis, rated among the top mortality reasons and its significance has been increasing progressively. Therefore, having a diagnostic tool to predict the cardiovascular diseases is prominent. The most common diagnostic tool for this type of disorders is using angiography; however, evaluating the Work of Heart is emerging as an easy to use and non-invasive tool recently. In this study, the modified Windkessel model and different whole blood viscosity models (Casson and Herschel-Bulkley) are employed to evaluate the heart work. The results revealed that both of the viscosity models can be used in conjunction with the modified Windkessel model.